Badania nad Starym Testamentem w „Collectanea Theologica” 1920-2020 - Chrostowski, Waldemar (Collectanea Theologica, 2020)
The articles devoted to the Old Testament scholarship and published in the oldest and most important Polish theological journal “Collectanea Theologica” are ordered according to three main periods, namely: Years 1920-1939; Years 1949-1989 and Years 1990-2020. In the framework of these periods they and presented in seven phases: 1. Years 1920-1930; 2. Years 1931-1939; 3. Years 1949-1965; 4. Years 1966-1978; 5. Years 1979-1989; 6. Years 1990-2003 and 7. Years 2004-2020. All titles of publications and their authors are mentioned, giving an idea of the history, results and scientific level of Polish biblical scholarship on the first part of the Christian Bible. It may be observed that huge progress, both in quantity and quality, was done in the last half century.